Challenges in halal food ecosystems: the case of the United Arab Emirates. Issue 5 (3rd June 2019) - Randeree, Kasim
Abstract : Purpose: The purpose of this paper is to investigate challenges in balancing interoperability, food quality and customer satisfaction in halal food supply chains. Design/methodology/approach: The study employed ethnography and grounded theory research methodologies. Research methods were ethnographic content analysis and document content analysis. The research framework encompassed a range of stakeholder groups connected with the halal food supply chain in the United Arab Emirates (UAE), focussing on Islamic jurisprudence, halal food sector analysis, import regulation compliance, halal food certification (HFC), food production, retailing and consumption. Findings: The research found that supply chain intermediaries are challenged in balancing interoperability issues around non-unified global certification standards. Consequent variability in customer confidence in halal standards was found. Research limitations/implications: This research focussed on the internal supply chain in the UAE, with future scope in HFC systems among external supplier nations and wider market research on customer perceptions of halal food integrity. Practical implications: Transferability of the findings is high; to other halal food markets in particular, as well as supply chain systems for halal products across other Islamic economy sectors, notably halal pharmaceuticals and cosmetics. Aligning the halal ecosystem with trends in healthy eating and environmentalism is also considered. Originality/value: The paper uniquely explores the halal food sector from the perspective of variant stakeholder disciplines in halal sector governance and operation. It exposes vulnerabilities in halal supply chains in a nation with one of the most demanding and diverse agri-food supply systems in the world.